2021
DOI: 10.1007/s13399-021-01473-2
|View full text |Cite
|
Sign up to set email alerts
|

Plant-based fructans for increased animal welfare: provision processes and remaining challenges

Abstract: Fructans are carbohydrates consisting of fructose monomers linked by β-2,1- and/or β-2,6-glycosidic bonds with linear or branched structure. These carbohydrates belong to the group of prebiotic dietary fibre with health-promoting potential for humans and mammals due to their indigestibility and selective stimulation of microorganisms in the gastrointestinal tract. This makes fructans interesting mainly for healthy food as well as animal feed applications. As a consequence of a growing public awareness for anim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 124 publications
(210 reference statements)
0
11
0
Order By: Relevance
“…Even though the fructan content is relatively low, this material flow (bioethanol stillage) is considered to be a true residue without any other competitive utilization so far. Against the background of increasing demand for prebiotics like fructans not only for human but also animal nutrition, such low-value residues could come into the focus (Zimmermann et al, 2021). Here, the established analytical method may be used for the investigation of respective fructan separation processes.…”
Section: Application Of the Developed Analytical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the fructan content is relatively low, this material flow (bioethanol stillage) is considered to be a true residue without any other competitive utilization so far. Against the background of increasing demand for prebiotics like fructans not only for human but also animal nutrition, such low-value residues could come into the focus (Zimmermann et al, 2021). Here, the established analytical method may be used for the investigation of respective fructan separation processes.…”
Section: Application Of the Developed Analytical Methodsmentioning
confidence: 99%
“…Besides plants, complex sample matrices like residues from industrial biomass processing (e.g., chicory roots; Zimmermann et al, 2021) can contain fructans. Thus, such residues can be promising resources for higher‐value products like prebiotics for feed and food applications.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the fructan content is relatively low, this material flow (bioethanol stillage) is considered to be a true residue without any other competitive utilisation so far. Against the background of an increasing demand for prebiotics like fructans not only for human but also animal nutrition, such low value residues could come into the focus [39]. Here, the established analytical method may be used for the investigation of respective fructan separation processes.…”
Section: Application Of the Developed Analytical Methodsmentioning
confidence: 99%
“…Besides plants, complex sample matrices like residues from industrial biomass processing (e.g., chicory roots [39]) can contain fructans. Thus, such residues can be promising resources for higher-value products like prebiotics for feed and food applications.…”
Section: Introductionmentioning
confidence: 99%
“…Several nutritional strategies have been identified to minimize the stress associated with abrupt weaning, such as optimizing energy levels of the diet and using feed additives (probiotics, prebiotics, SCFA, phytogenic compounds and nucleotides) post-weaning (7,9). Several studies (10)(11)(12)(13)(14) have reported the beneficial effects of several prebiotics such as inulin, fructans, fructo-/galactooligosaccharides, and resistant starch on weaning animals, such as boosting intestinal immunity, regulating microbial fermentation, and modulating intestinal tight junction in weaned piglets. In recent years, there has been a growing body of literature that highlights the importance of prebiotics for easing the impact of weaning stress in young animals.…”
Section: Introductionmentioning
confidence: 99%